Antibiotics manual a guide to commonly used antimicrobials - Schlossberg, David; Samuel, Rafik (John Wiley & Sons Ltd., 2017)
The visual design of this manual aids the rapid retrieval of information and makes it possible to offer more information than the popular 'Sanford Guide', while focusing on the essentials and eliminating the details covered in standard textbooks. It includes 188 of the most common agents used in internal medicine by drug name